Research of weak signal detection based on super‐regenerative chaotic oscillator. Issue 5 (10th December 2021) - Yang, Yifan; Xu, Jian; Kuang, Yun; Tu, Hanfen; Wei, Haoran; Yang, Hao; Min, Ke; Yang, Wenliang
Abstract: Under certain circumstances, chaos will occur in the super‐regenerative receiver. The gain of the receiver reaches the maximum and the receiver is immune to the external noise in this case. The concept of super‐regenerative chaotic oscillator is proposed, and its potential capability of detection for the weak signal is studied for the first time. The simulation results show that, under the same input SNR, the signal sensitivity of the super‐regenerative chaotic oscillator is up to 40dB higher than that of the ordinary super‐regenerative oscillator, which means that it has stronger noise suppression and more sensitive response to the signal submerged in the noise. It shows its potential application value for the weak signal detection.